Academies as the ‘future of schooling’: is this an evidence-based policy? - Gorard, Stephen (Journal of Education Policy, 2005)
A programme of City Academies was announced by the Secretary of State for Education for England in 2000. These schools would be independent of local government control, have voluntary and private sector sponsors, and would break the cycle of failing inner-city schools. The first three Academies opened in 2002, and this paper considers how they have fared so far in terms of changes to their student intake and improvements in examination outcomes. Using figures from 1997 to 2003–2004 from the annual school census and from the DfES Standards site, the paper shows that there is no evidence that these schools are, in general, performing any better for equivalent students than the schools they replaced. Although the programme is at a very early stage, this finding is important because it contradicts the claims of the DfES and of the Academies themselves and the determination of the government (at time of writing) to expand the programme to 200 schools.
Keywords: Grande Bretagne; méthodes de recherche; politique éducative; utilisation des recherches